2014
DOI: 10.1021/ac4033164
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Quantification of Proteins Secreted by Artificial Connective Tissue Made from Uni- Or Multidirectional Collagen I Scaffolds and Oral Mucosa Fibroblasts

Abstract: Previously, we found that oral autologous artificial connective tissue (AACT) had a different protein secretion profile to that of clot-embedded AACT. Other oral mucosa substitutes, having different cell types and scaffolds, had dissimilar secretion profiles of proteins (including that for AACT) that influence healing outcome; thus, to ascertain the profiles of factors secreted by artificial tissue and whether they are influenced by their microstructure might help in understanding their bioactivity. An importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…To determine the different TH1 responses from cells circulating in the blood, Rice and colleagues used SPR imaging [231]. Bustos measured growth factors secreted from cells using SPR [232]. Using unique protein-engineered albumin binding protein, interferon-γ (IFN-γ) has been measured to the 0.2 nM level using SPR [233].…”
Section: Optical Methodsmentioning
confidence: 99%
“…To determine the different TH1 responses from cells circulating in the blood, Rice and colleagues used SPR imaging [231]. Bustos measured growth factors secreted from cells using SPR [232]. Using unique protein-engineered albumin binding protein, interferon-γ (IFN-γ) has been measured to the 0.2 nM level using SPR [233].…”
Section: Optical Methodsmentioning
confidence: 99%
“…This may be because the increased staining was concomitant with an increase in cell number, indicating that cellular concentrations were likely unaltered. Bustos et al 36 showed that cytokines that regulate inflammation, angiogenesis, epithelialization, matrix remodeling, and deposition were secreted from oral fibroblasts seeded onto collagen I scaffolds and these secretions were affected by cellular alignment and distribution, as well as the fiber orientation of the collagen microstructure. Although we have used collagen I gel as a substrate for oral mucosa epithelial cells and mesenchymal cell scaffolds in this study, most of the gel layer was positive for Coll IV, whereas the epithelial basement membrane was not strongly stained (Figure 4b).…”
Section: Discussionmentioning
confidence: 99%
“…An ELISA of the same samples was carried out to evaluate the accuracy of SPR measurements. All the proteins evaluated were quantified with SPR, whereas with ELISA, only three were detected and quantified, which indicated that the sensitivity of the SPR methodology was higher than that of the ELISA methodology (Bustos, Suesca, Millán, González, & Fontanilla, ). Other published works have also shown that SPR is more sensitive than ELISA in the analysis of complex biological samples such as serum and urine (Avramis, Avramis, Hunter, & Long, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 97%
“…Our in vitro work with unidirectional and multidirectional oral artificial tissue also showed differences in morphology and alignment of fibroblasts depending upon the directionality of the scaffolds' fibres/pores. Oral fibroblasts seeded into collagen type I scaffolds with unidirectional oriented pores were elongated and aligned parallel to the fibres, whereas the ones seeded into scaffolds with multidirectional oriented pores were not elongated and showed a random distribution all over the scaffold (Bustos et al, ). The significant modification in the concentration of the healing mediating factors and the differences in morphology and alignment of the cells found suggested that when the unidirectional and multidirectional artificial tissues are grafted into a wound, they modulate the healing differently because of the concentration difference induced by the directionality of the fibres/pores of the scaffolds.…”
Section: Introductionmentioning
confidence: 99%